Does microplastic ingestion by zooplankton affect predator-prey interactions? An experimental study on larviphagy. (January 2020) - Van Colen, Carl; Vanhove, Brecht; Diem, Anna; Moens, Tom
Abstract: Litter is omnipresent in the ocean where it can be ingested by marine biota. Although ingestion of microplastics (MPs) is abundantly reported, insights into how MP can influence predator-prey interactions currently limits our understanding of the ecological impact of MPs. Here we demonstrate trophic transfer of MPs from zooplankton to benthic filter feeders, through consumption of contaminated prey (i.e. prey with ingested MP). However, predation rates of contaminated prey were significantly lower as compared to predation rates of prey that had no MPs ingested. As filter feeder clearance rates were not affected by consumption of MPs, the lower predation rates of contaminated prey appear to be primarily explained by disruption in zooplankton swimming behaviour that reduces their filtration risk. This is the first study that shows how MPs can change predator-prey interactions that are involved in the coupling between the pelagic and seabed habitat. Graphical abstract: Image 10760 Highlights: Trophic transfer of 4.8 μm PS beads from zooplankton to benthic filter feeders. Predation rates of contaminated prey are reduced by 30%. Disruption in prey behaviour likely explains the change in trophic interactions. Abstract : We demonstrate the trophic transfer of MPs from zooplankton to benthic filter feeders, highlighting that the presence of MPs can alter the transfer of energy between trophic levels.